Pelatihan Pembuatan Search Engine Optimization (SEO) sebagai Upaya Mengoptimalkan Pemasaran Digital UMKM - Martiyanti, Dwi; Alghifari, Muhammad Farhan; Aisyah, Sayyidah (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to increase the knowledge and skills of Daengta Roti Balikpapan MSME managers in optimizing digital marketing through the use of Search Engine Optimization (SEO). The method of implementing this service uses training, which includes socialization, discussion, and mentoring. The target of this activity is to strive for optimal use of the Google site through SEO to increase visitors and buyers. The evaluation instrument for this activity uses a questionnaire and is analyzed descriptively. The results of this service show that Daengta Roti Balikpapan MSMEs have the knowledge and skills to operate and manage SEO well. MSME players also understand the steps to attract and increase the number of visits through Search Engine Optimization (SEO) by adding descriptions for products, adding information on Google Maps, connecting to Instagram or Facebook, and creating a Google site.